A method for preparing a piezoelectric nanogenerator
Porous zinc oxide is prepared by electrospinning method and is compounded with silver nanowires and silicone to form a piezoelectric composite film, which solves the problem of low piezoelectric output performance of existing zinc oxide nanowire array piezoelectric nanogenerators, and realizes the preparation of a high-performance porous zinc oxide/silver nanowire piezoelectric nanogenerator.
Patent Information
- Application Number
- CN202210947237.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-09
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-08-09
AI Technical Summary
The existing zinc oxide nanowire array piezoelectric nanogenerators and zinc oxide p-n junction piezoelectric nanogenerators have problems such as low piezoelectric output performance and complex device preparation technology.
Porous zinc oxide is prepared by electrospinning method, and is compounded with silver nanowires and silicone to form a piezoelectric composite film. Finally, it is dripped on the substrate and cured in vacuum to bond the conductive electrode to prepare a porous zinc oxide/silver nanowire piezoelectric nanogenerator.
Through the formation of pore structure and the conductive network of silver nanowires, the piezoelectric shielding effect is effectively suppressed, the piezoelectric performance is improved, and the preparation process is simple and controllable. The resulting device has excellent piezoelectric performance, flexibility and cyclic stability.
Smart Images

Figure CN115360294B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of piezoelectric devices, and in particular relates to a method for preparing a piezoelectric nanogenerator. Background Art
[0002] The development of new wearable flexible electronics and wireless technologies has led to an increasing interest in portable power sources. Among various sustainable energy generators, flexible piezoelectric nanogenerators have become a hot topic in the current research of flexible wearable power sources due to their advantages such as renewability, wear resistance, portability and self-powering capability. Among many piezoelectric materials, zinc oxide has become one of the most studied materials due to its excellent piezoelectric effect, good safety and biocompatibility. It can be designed into miniaturized, flexible and integrated devices and has a wide range of applications in self-powered devices such as sensors and nanogenerators. The thermodynamically stable phase of zinc oxide is the wurtzite structure. Due to its large anisotropy in the c-axis and perpendicular c-axis directions, when the crystal is subjected to external force in the c-axis direction, due to the lack of central symmetry in zinc oxide, the positive and negative charge centers are separated to produce dipole moments. The superposition of all dipole moments leads to a macroscopic potential drop along the crystal strain direction, thus showing good piezoelectric response performance.
[0003] However, zinc oxide is a natural n-type semiconductor, which contains inherent defects and impurity atoms, which will introduce a large number of free carriers. These free carriers offset the positive potential when generating piezoelectric potential, resulting in a piezoelectric shielding effect, thereby reducing the piezoelectric potential.
[0004] The zinc oxide nanowire array piezoelectric nanogenerators and zinc oxide pn junction piezoelectric nanogenerators reported in the existing literature have the problems of low piezoelectric output performance and complex device preparation process. Therefore, it is of great significance to use a simple method to prepare high-performance zinc oxide-based flexible piezoelectric nanogenerators. Summary of the invention
[0005] The present invention provides a method for preparing a piezoelectric nanogenerator to solve the technical problems of the prior art that the preparation process is complex and the piezoelectric performance is poor.
[0006] To achieve the above object, the embodiments of the present invention adopt the following technical solutions:
[0007] The present invention provides a method for preparing a piezoelectric nanogenerator, comprising the following steps:
[0008] A. Dissolve polyvinyl pyrrolidone in ethanol, add zinc acetate and deionized water, and stir until the solution becomes colorless and transparent to obtain a precursor solution;
[0009] B. electrospinning the precursor solution obtained in step A to obtain a precursor fiber membrane;
[0010] C. Drying and calcining the precursor fiber membrane obtained in step B to obtain porous zinc oxide;
[0011] D. Mix the porous zinc oxide obtained in step C with the silver nanowire dispersion and silica gel to obtain a slurry, and then drop-coat the slurry on the substrate. After vacuum curing, a piezoelectric composite film is obtained.
[0012] E. Bonding conductive electrodes on both sides of the piezoelectric composite film obtained in step D to obtain a piezoelectric nanogenerator.
[0013] The present invention has the following beneficial effects:
[0014] The present invention provides a method for preparing a piezoelectric nanogenerator based on porous zinc oxide and silver nanowires. The porous zinc oxide prepared by electrospinning and sintering is used as the piezoelectric material, and nano silver wires are selected as the conductive filler. The two are compounded with silica gel to obtain a piezoelectric composite film, and copper foils are bonded to both sides of the piezoelectric composite film to obtain a porous zinc oxide / silver nanowire piezoelectric nanogenerator. The invention has the following beneficial effects: (1) during sintering of the precursor fiber membrane obtained by electrospinning, polyvinyl pyrrolidone decomposes and forms holes on the zinc oxide fiber. The formation of holes can increase the deformation of the zinc oxide fiber under stress, thereby improving the piezoelectric performance; (2) silver nanowires with a high aspect ratio serve as conductive fillers in the piezoelectric composite material, forming a highly conductive bridging network in the device (piezoelectric nanogenerator), and a Schottky contact is formed between the silver nanowires and the zinc oxide. When the device is stressed and generates a piezoelectric potential, under the action of non-electrostatic forces, due to the presence of the silver nanowire conductive network, free carriers are easy to flow and transfer to the metal negative electrode, effectively suppressing the piezoelectric shielding effect and improving the piezoelectric performance; (3) the sintering process plays an annealing role, and the prepared porous zinc oxide has good crystallinity, which means fewer free carriers, which is conducive to reducing the piezoelectric shielding effect; (4) the preparation process provided by the invention is simple and controllable, and the obtained flexible piezoelectric nanogenerator has excellent piezoelectric performance, and also has the advantages of good cycle stability, ultra-high flexibility, etc.
[0015] In some embodiments, in step A, the mass ratio of polyvinyl pyrrolidone to zinc acetate is 1:1.
[0016] In some embodiments, in step A, the stirring temperature is 60-65° C., and the rotation speed is 300-350 rpm.
[0017] In some embodiments, in step B, during the electrospinning, the flow rate is 24 mL / h, the voltage is 18-20 kV, the distance between the needle and the receiver is 10-15 cm, and the humidity of the spinning environment is 30-40%.
[0018] In some embodiments, in step C, the drying temperature is 70-80°C, the time is 1.5-2h, the calcination temperature is 700-750°C, the heating rate is 6°C / min, and the holding time is 5h.
[0019] In some embodiments, in step E, the mass ratio of the porous zinc oxide to the silver nanowire dispersion and the silica gel is 2:1:4.
[0020] In some embodiments, the mass fraction of the silver nanowire dispersion is 0.28%.
[0021] In some embodiments, in step D, the slurry is dripped on the substrate to a thickness of 2 mm and the curing time is 6 hours.
[0022] In some embodiments, in step E, the conductive electrode is a copper foil. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 is the SEM morphology of the porous zinc oxide fiber in Example 2;
[0025] Figure 2 is the XRD pattern of the porous zinc oxide fiber in Example 2;
[0026] Figure 3a is a graph of the output voltage of the piezoelectric generator based on commercial zinc oxide powder in Comparative Example 1;
[0027] Figure 3b is a graph of the output current of the piezoelectric generator based on commercial zinc oxide powder in Comparative Example 1;
[0028] Figure 4a is a graph of the output voltage of the porous zinc oxide piezoelectric nanogenerator in Example 1;
[0029] Figure 4b is the output current diagram of the porous zinc oxide piezoelectric nanogenerator in Example 1;
[0030] Figure 5a is a graph of the output voltage of the porous zinc oxide / silver nanowire piezoelectric nanogenerator in Example 2;
[0031] Figure 5b is an output current diagram of the porous zinc oxide / silver nanowire piezoelectric nanogenerator in Example 2;
[0032] Figure 6 is a graph of the output voltage generated by the porous zinc oxide / silver nanowire piezoelectric nanogenerator in Example 2 after cyclic impact-release;
[0033] Figure 7 These are the flexibility test data and actual pictures of the porous zinc oxide / silver nanowire piezoelectric nanogenerator in Example 2. DETAILED DESCRIPTION
[0034] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0035] In this application, the silica gel is purchased from Beijing Sanjing Xinde Technology Co., Ltd., the product name is super transparent AB glue, model number is SJ3213-A, and the commercial zinc oxide powder is purchased from Guangzhou Liben Rubber Raw Materials Trading Co., Ltd., and the purity of zinc oxide is ≥99.7%.
[0036] Comparative Example 1
[0037] This comparative example provides a method for preparing a piezoelectric generator based on commercial zinc oxide powder, comprising the following steps:
[0038] 1g of commercial zinc oxide powder was evenly mixed with 2g of silica gel and cured for 6 hours to obtain a piezoelectric composite film based on commercial zinc oxide. Copper foil electrodes were bonded to the upper and lower surfaces of the piezoelectric composite film to obtain a piezoelectric generator based on commercial zinc oxide powder.
[0039] Example 1
[0040] Under magnetic stirring at 60°C, 0.8g of polyvinyl pyrrolidone powder was mixed with 10mL of ethanol until the polyvinyl pyrrolidone was completely dissolved to obtain a polyvinyl pyrrolidone solution. 0.8g of zinc acetate and 1mL of deionized water were added dropwise to the above polyvinyl pyrrolidone solution, and stirring was continued until the solution was colorless and transparent to obtain a precursor solution. The precursor solution was loaded into a syringe connected to the positive electrode of the power supply, the injection flow rate was controlled at 24mL / h, the humidity was controlled at 35%, the working distance between the needle and the receiver was 10cm, the applied voltage was 20kV, and the precursor fiber membrane was obtained after spinning. The precursor fiber membrane was dried in a 70°C oven, and the dried fiber membrane was placed in a high-temperature tubular furnace and calcined at 700°C in an air atmosphere for 5h to obtain porous zinc oxide. 1g of porous zinc oxide was evenly mixed with 2g of silica gel and cured for 6h to obtain a porous zinc oxide flexible piezoelectric composite film. Copper foil electrodes were bonded to the upper and lower surfaces of the flexible piezoelectric composite film to obtain a piezoelectric generator based on porous zinc oxide.
[0041] Example 2
[0042] Under magnetic stirring at 60°C, 0.8g of polyvinyl pyrrolidone powder was mixed with 10mL of ethanol until the polyvinyl pyrrolidone was completely dissolved to obtain a polyvinyl pyrrolidone solution. 0.8g of zinc acetate and 1mL of deionized water were added dropwise to the above polyvinyl pyrrolidone solution, and stirring was continued until the solution was colorless and transparent to obtain a precursor solution. The precursor solution was loaded into a syringe connected to the positive electrode of the power supply, the injection flow rate was controlled at 24mL / h, the humidity was controlled at 35%, the working distance between the needle and the receiver was 10cm, the applied voltage was 20kV, and the precursor fiber membrane was obtained after spinning. The precursor fiber membrane was dried in a 70°C oven, and the dried fiber membrane was placed in a high-temperature tubular furnace and calcined at 700°C in an air atmosphere for 5h to obtain porous zinc oxide. Take 10mL of 0.1M AgNO3 ethylene glycol solution, 10mL of 0.15M polyvinyl pyrrolidone ethylene glycol solution, 40μL of 0.1M NaCl ethylene glycol solution, 15μL of 0.1M NaBr ethylene glycol solution, 5μL of 0.01M Fe(NO3)3 ethylene glycol solution, stir at 25℃ and 300rpm for 2min to mix evenly to obtain AgNO3 precursor solution. Transfer the Ag NO3 precursor solution to a hydrothermal reactor and react at 160℃ for 3h to obtain silver nanowires, which are dispersed in anhydrous ethanol to obtain a silver nanowire dispersion. Evenly mix 1g of porous zinc oxide, 0.5g of silver nanowire dispersion and 2g of silica gel, and solidify for 6h to obtain a porous zinc oxide / silver nanowire piezoelectric composite film. Bond copper foil electrodes on the upper and lower surfaces of the piezoelectric composite film to obtain a porous zinc oxide / silver nanowire piezoelectric nanogenerator.
[0043] The piezoelectric performance test method of the piezoelectric nanogenerator prepared in the present invention uses a single-axis motion controller to apply a stress of 9.25 kPa to the piezoelectric nanogenerator, and the stress is kept constant during the entire test process. The specific test results are analyzed as follows:
[0044] Figure 1 This is a morphology diagram of the porous zinc oxide fiber of Example 2. It can be seen from the figure that the microporous structure is evenly distributed on the zinc oxide fiber matrix.
[0045] Figure 2 The XRD pattern of the porous zinc oxide fiber of Example 2. In the XRD pattern of the porous zinc oxide fiber in the range of 20°-80°, the diffraction peaks are located at 31.94°, 34.58°, 36.39°, 47.67° and 56.78°, corresponding to the (100), (002), (101), (102) and (110) crystal planes of wurtzite zinc oxide (JCPDS 36-1451 card), respectively. The sharp diffraction peaks indicate that the porous zinc oxide has good crystallinity, which means fewer free carriers, which is conducive to weakening the piezoelectric shielding effect.
[0046] Depend on Figure 3a , Figure 3b , Figure 4a and Figure 4b It can be seen that the output voltage peaks of the piezoelectric generator based on commercial zinc oxide powder and the piezoelectric generator based on porous zinc oxide are 6.48V and 85V, respectively, and the output current peaks are 0.15μA and 0.78μA, respectively. This shows that the pore structure of zinc oxide piezoelectric materials will promote the improvement of piezoelectric performance.
[0047] Figure 5a and Figure 5b The output voltage and output current diagrams of the porous zinc oxide / silver nanowire piezoelectric nanogenerator are shown in Figure 1. As shown in the figure, the output voltage signal and current signal of the piezoelectric nanogenerator doped with silver nanowires are further increased, which are 146V and 1.08μA, respectively. Compared with the porous zinc oxide piezoelectric nanogenerator without silver nanowires, the output voltage and current amplitudes are increased by 71.7% and 38.5%, respectively. This is mainly because the silver nanowires, as good conductive fillers in piezoelectric composite materials, form a conductive lap network in the device, and a Schottky contact is formed between the silver nanowires and zinc oxide. When the piezoelectric potential is generated by external force, under the action of non-electrostatic force, the free carriers can easily flow and transfer to the metal negative electrode, effectively suppressing the piezoelectric shielding effect and improving the piezoelectric performance.
[0048] Figure 6This is the output voltage curve of the porous zinc oxide / silver nanowire piezoelectric nanogenerator after 5000 cycles of impact-release. As can be seen from the figure, after 5000 cycles of impact, the voltage amplitude of the generator remains stable, which means that the porous zinc oxide / silver nanowire piezoelectric nanogenerator shows excellent stability under long-term stress excitation and has a long service life.
[0049] Figure 7 This is the flexibility test data of the porous zinc oxide / silver nanowire piezoelectric nanogenerator. It can be seen from the figure that the porous zinc oxide / silver nanowire piezoelectric nanogenerator can achieve large-angle bending, twisting or ultra-long stretching, and can generate different voltage and current responses while deforming. This means that the porous zinc oxide / silver nanowire piezoelectric nanogenerator has excellent flexibility and wearability.
[0050] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope of the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a piezoelectric nanogenerator, characterized in that: The following steps are involved: A. Dissolve polyvinyl pyrrolidone in ethanol, add zinc acetate and deionized water, and stir until the solution becomes colorless and transparent to obtain a precursor solution; B. electrospinning the precursor solution obtained in step A to obtain a precursor fiber membrane; C. Drying and calcining the precursor fiber membrane obtained in step B to obtain porous zinc oxide; D. Mix the porous zinc oxide obtained in step C with the silver nanowire dispersion and silica gel to obtain a slurry, and then drop-coat the slurry on the substrate. After vacuum curing, a piezoelectric composite film is obtained. E. Bonding conductive electrodes on both sides of the piezoelectric composite film obtained in step D to obtain a piezoelectric nanogenerator.
2. The preparation method according to claim 1, characterized in that: In step A, the mass ratio of polyvinyl pyrrolidone to zinc acetate is 1:
1.
3. The preparation method according to claim 1, characterized in that: In step A, the stirring temperature is 60-65° C. and the rotation speed is 300-350 rpm.
4. The preparation method according to claim 1, characterized in that: In step B, during the electrospinning, the flow rate is 24 mL / h, the voltage is 18-20 kV, the distance between the needle and the receiver is 10-15 cm, and the humidity of the spinning environment is 30-40%.
5. The preparation method according to claim 1, characterized in that: In step C, the drying temperature is 70-80°C, the time is 1.5-2h, the calcination temperature is 700-750°C, the heating rate is 6°C / min, and the holding time is 5h.
6. The preparation method according to claim 1, characterized in that: In step D, the mass ratio of the porous zinc oxide to the silver nanowire dispersion and the silica gel is 2:1:
4.
7. The preparation method according to claim 6, characterized in that: The mass fraction of the silver nanowire dispersion is 0.28%.
8. The preparation method according to claim 1, characterized in that: In step D, the slurry is dripped onto the substrate to a thickness of 2 mm and the curing time is 6 h.
9. The preparation method according to claim 1, characterized in that: In step E, the conductive electrode is copper foil.
Citation Information
Patent Citations
Method for preparing zinc oxide composite material with high specific surface area and zinc oxide composite material
CN104671277A
Preparation method of zinc oxide / carbon composite material for negative electrode of lithium-ion battery
CN108063240A